Computerized adaptive testing in kinanthropology : Monte Carlo simulations using physical self-description questionnaire - Komarc, Martin (Charles University, Karolinum Press, 2018)
This book aims to introduce the use of computerized adaptive testing applied to the field of Kinanthropology. Nakladatelská anotace. Kráceno
Keywords: Computer Simulation; průzkumy a dotazníky; Surveys and Questionnaires; statistika, zdravotnická statistika; počítačová simulace; Data Interpretation, Statistical; psychometrie; Psychometrics; interpretace statistických dat